Alterations in the structural characteristics of rectus abdominis muscles caused by diabetes and pregnancy: A comparative study of the rat model and women - Vesentini, Giovana [UNESP]; Barbosa, Angélica M.P. [UNESP]; Damasceno, Débora C. [UNESP]; Marini, Gabriela [UNESP]; Piculo, Fernanda [UNESP]; Matheus, Selma M.M. [UNESP]; Hallur, Raghavendra L.S. [UNESP]; Nunes, Sthefanie K. [UNESP]; Catinelli, Bruna B. [UNESP]; Magalhães, Claudia G. [UNESP]; Costa, Roberto [UNESP]; Abbade, Joelcio F. [UNESP]; et al. (Public Library of Science (PLoS), 2020)
Background and objective In the present study, we compared the effect of diabetic pregnancy on the rectus abdominis muscle (RAM) in humans and rats. We hypothesized that our animal model could provide valuable information about alterations in the RAM of women with Gestational Diabetes (GDM). Method Newborns female rats (n = 10/group) were administered streptozotocin (100 mg/kg body weight) subcutaneously and were mated on reaching adulthood, to develop the mild hyperglycemic pregnant (MHP) rat model. At the end of pregnancy, the mothers were sacrificed, and the RAM tissue was collected. Pregnant women without GDM (non-GDM group; n = 10) and those diagnosed with GDM (GDM group; n = 8) and undergoing treatment were recruited, and RAM samples were obtained at C-section. The RAM architecture and the distribution of the fast and slow fibers and collagen were studied by immunohistochemistry. Results No statistically significant differences in the maternal and fetal characters were observed between the groups in both rats and women. However, significant changes in RAM architecture were observed. Diabetes in pregnancy increased the abundance of slow fibers and decreased fast fiber number and area in both rats and women. A decrease in collagen distribution was observed in GDM women; however, a similar change was not observed in the MHP rats. Conclusion Our results indicated that pregnancy- associated diabetes- induced similar structural adaptations in the RAM of women and rats with slight alterations in fiber type number and area. These findings suggest that the MHP rat model can be used for studying the effects of pregnancy-associated diabetes on the fiber structure of RAM.